ANALYSYS ORGAN OF SPEECH IN PRONUNCIATION - Firza Sakinah; Nicky Aulia; Yani Lubis (Cendekia Madani Nusantara, 2024)
ABSTRAK Uncovering Speech Organs to Learn Pronunciation. The art of pronunciation, or giving words life, is a sophisticated symphony that the human body performs. Today, we set out on a quest to discover this hidden orchestra, dissecting how these organs' delicate movements shape the variety of sounds we utilize to Talk to each other. In a similar vein, speakers modify the airflow across the vocal tract to produce various sounds. The raw material is provided by the lungs, which force the air upward. As a conductor, the larynx—which houses the vocal cords— determines whether the air is spoken or unvoiced, causing vibrations. Then, the tongue, lips, and jaw work together like a master sculptor, forming the air flow through a variety of cavities and constrictions to produce the distinct vowel and consonant sounds that comprise spoken language. The objective of this journal's use of qualitative methodologies is to comprehend an organ of speech phenomena, which will be covered in greater detail later on. The scientific study of speech sounds is known as phonetics. The study of speech sound creation, transmission,and reception is another way to define phonetics. Key: Speech organ, Articullation, Phonetics, Part of organ speech